Related factors of postnatal growth failure upon hospital discharge among low-birth-weight infants in Eastern Indonesia - Suni Hariati; Erfina; Lely Lusmilasari (Universitas Airlangga, 2026)
Introduction: Postnatal growth failure is common among low birth weight (LBW) infants, impacting their childhood catch-up growth and development. This study aimed to identify factors associated with postnatal growth failure at hospital discharge among LBW infants. Methods: A cross-sectional design was employed, examining medical records of LBW infants from July 2023 to 2024 at seven hospitals in Indonesia. Records included infants with birth weights under 2500 grams treated in SCNU and/or NICU, excluding those with incomplete data, readmissions, or referrals. Descriptive and logistic regression analyses identified factors related to postnatal growth failure.Results: The study reviewed 161 LBW infants to identify growth failure factors at discharge. Most were preterm, with 65.2% delivered by cesarean section. Significant risk factors included gestational age (OR 4.215; P-value .002), birth growth category (OR 6.155; P-value .006), and nasal oxygen history (OR 2.869; P-value .023). Preterm infants had a 4.2 times higher risk of growth failure, while small-for-gestational-age (SGA) infants had a 6.2 times higher risk than appropriate-for-gestational-age (AGA) infants. The length of hospitalization and type of nutrition showed no statistical significance.Conclusion: Preterm and SGA infants are at higher risk of postnatal growth failure at discharge. Enhancing family-centered care, nutritional support, infection prevention, and interdisciplinary collaboration is crucial for improvement in SCNU/NICU.Keywords: low birth weight, growth failure, hospital discharge, postnatal, preterm infant